Pengembangan Game Action Sejarah Kerajaan Siak Sri Indrapura Bergenre Role Play Game - Ahmad Fauzan; Nazruddin Safaat H; Muhammad Irsyad; Pizaini Pizaini (STMIK Banjarbaru, 2022)
Many people do not know how the history of the Kingdom of Siak Sri Indrapura was founded. There are also very few historical sources in written form, most historical sources are still in oral form. There fore the author builds a game that can be used by the public, which contains elements of the history of the Siak kingdom. This is intended so that the history of the Siak kingdom does not just disappear. This is very important to do so that people want to preserve and know the history of the Siak Kingdom. This game was built using the Research & Development method and using Unreal Engine 4 software which can be run on the Desktop platform, the results of testing with BlackBox and the User Acceptance Test to test it obtained a value of 93%. These results state that the Action Game History of the Work of Siak Sri Indrapura with the genre of Role Play Game (RPG) developed can be a fun learning medium and increase people's desire to know more about the history of the Kingdom of Siak in Riau.Keywords: Siak Kingdom; Role Play Game; Desktop Platform; Unreal Engine 4; Blackbox TestingAbstrakBanyak masyarakat yang belum mengetahui bagaimana sejarah Kerajaan Siak Sri Indrapura berdiri. Sumber sejarah juga masih sangat sedikit dalam bentuk tulisan, kebanyakan sumber sejarah masih dari bentuk lisan. Oleh karena itu penulis membangun sebuah game yang dapat digunakan oleh masyarakat, dimana di dalamnya mengandung unsur sejarah kerajaan Siak. Hal ini bertujuan agar sejarah kerajaan Siak tidak hilang begitu saja, Ini sangat penting dilakukan agar masyarakat mau melestarikan dan mengetahui sejarah Kerajaan Siak. Game ini di bangun dengan metode Research & Development dan menggunakan software Unreal Engine 4 yang di dapat dijalankan pada platform Dekstop, hasil dari pengujian dengan BlackBox dan User Acceptance Test untuk mengujinya didapatkan nilai 93%. Hasil ini menyatakan bahwa Game Action Sejarah Kerjaan Siak Sri Indrapura bergenre Role Play Game (RPG) yang dikembangkan dapat menjadi media pembelajaran yang menyenangkan serta meningkatkan keinginan masyarakat untuk lebih mengenal sejarah Kerajaan Siak di Riau.